ACUTE TOXICITY EVALUATION OF ETHANOL EXTRACT OF INDONESIAN VELVET BEANS - Sardjono, Ratnaningsih Eko; Musthapa, Iqbal; ., Sholihin; Qowiyah, Atun; Rachmawati, Rahmi (International Journal of Pharmacy and Pharmaceutical Sciences, 2017)
Objective: This research was conducted to determine the acute toxicity of ethanol extract of velvet beans (Mucuna pruriens) from Indonesia. Extract of Indonesian Mucuna pruriens seeds showed antiparkinson activity due to the presence of L-DOPA inadequate levels. However, research on the toxicity level of Mucuna pruriens seeds from Indonesia is still limited. Acute toxicity data are needed to make Mucuna pruriens as standardized herbal medicine for Parkinson disease. Methods: The dried seed of Mucuna pruriens was extracted by ethanol and suspended with tragacanth to make several dosas of ethanol extract of Mucuna pruriens seeds. Determination of acute toxicity was performed on six groups, each consisting of five Wistar rats. One group was used as a control group; other groups were given ethanol extract of Mucuna pruriens seeds orally at a dose of 5 mg/kg, 50 mg/kg, 300 mg/kg, 2000 mg/kg, and 5000 mg/kg body weight. Symptoms of toxicity, including death, were observed daily for 14 d. At the end of the observation, the surviving Wistar rats were autopsied and the brain, heart, liver, lungs, stomach, spleen, kidneys, and ovaries were weighed to give relative organ weight. Results: There was no mortality observed in all groups. The Wistar rats gained weight within the normal range. The relative organ weights in all groups generally did not show a significant difference. However, the significant differences (P<0.05) were seen in the liver for all treatment groups compared to the control group. Conclusion: The ethanol extract of Mucuna pruriens seeds from Indonesia administered orally has LD50>5000 mg/kg, thus it could be regarded as safe or non-toxic. However, this extract may be potentially toxic to the liver